Dissecting the Molecular Function of Triticum aestivum STI Family Members Under Heat Stress - Meena, Shaloo; Deb, Sohini; Samtani, Harsha; Khurana, Paramjit (Frontiers in Genetics, 2020)
STI/HOP functions as a co-chaperon of HSP90 and HSP70 whose molecular function has largely being restricted to as an adaptor protein. However, its role in thermotolerance is not well explored. In this article, we have identified six members of TaSTI family, which were named according to their distribution on chromosome 2 and 6. Interestingly, TaSTI-2 members were found to express higher as compared to TaSTI-6 members under heat stress conditions, with TaSTI-2A being the most heat responsive member. Consistent with this, ectopic overexpression of TaSTI-2A in Arabidopsis resulted in enhanced basal as well as acquired thermotolerance as revealed by the higher yield of the plants under stress conditions. Similarly in case of rice, TaSTI-2A transgenics exhibited enhanced heat stress tolerance. Moreover, we demonstrate that TaSTI-2A interacts with TaHSP90 not only in the nucleus but also in the ER and Golgi bodies, which has not been shown till now. Interestingly, TaHSP70 was also found to interact with TaSTI-6D specifically in the cytosol. Thus, these data together suggest that the TaSTI family members might play different roles under heat stress conditions in order to fine tune the heat stress response.